Fishing gears and crafts used in Gumti river of Muradnagar upazila, Bangladesh - Sakib, Md Nazmus; Hasan, Md Robiul; Ullah, Md Akram (Asian Journal of Medical and Biological Research, 2020)
The study describes traditional fishing gears and crafts available at Gumti river of Muradnagarupazila in Cumilla district, Bangladesh. The study was carried out by the collection of primary data through surveying individual fishermen. We found that there are 6 fishing gears available in the study area. Among them, 5 types of the fishing net (i.e., cast nets, seine net, lift net, push net, gill net) and a kind of fishing trap was identified. We also found 4 different types of crafts, including dinginauka, koshanauka, chandinauka, and sototempu. Synthetic twines are used for net making, which increases the fishing efficiency significantly. The life span of these nets varies according to their building materials. Sun-drying was the best approach for net preservation rather than using any chemicals or medicine. Besides, traditionally mehogany, raintree, shill koroi, garjan, gamari, jarul, chapulis woods and bamboos were found to be boat construction materials. The boats are painted with tar or pitch and burn oil for the protection. No modern instruments such as a compass, life-saving equipment are used by these boats. Most of the boats are mechanized, i.e. operated by engine. Asian J. Med. Biol. Res. September 2020, 6(3): 469-474